Editorial: modelling approaches for climate variability and change mitigation and adaptation in resource constrained farming systems - Mkuhlani, S.; Kephe, P. N.; Rusere, F.; Ayisi, K. (Frontiers Media, 2024)
The impacts of climate variability and change are disproportionately experienced in the Global South, particularly within resource-constrained smallholder farming systems (Ngcamu, 2023; Asare-Nuamah, 2021). Smallholder farmers, who play a critical role in local economies and food systems, are increasingly vulnerable to erratic weather patterns, extreme temperatures, and prolonged droughts, which threaten both their food security and livelihoods (Touch et al., 2024). To address these challenges, there is an urgent need to develop, evaluate, and implement low-cost, adaptable climate risk management strategies. The Research Topic, “Modelling Approaches for Climate Variability and Change Mitigation and Adaptation in Resource-Constrained Farming Systems,” aimed to leverage modeling tools and approaches, such as crop models, machine learning, and big data analysis to identify and evaluate cost-effective climate risk management and mitigation strategies. These strategies aim to enhance the resilience and decision-making capacity of smallholder farmers in the global South.